2006
DOI: 10.1038/sj.onc.1209593
|View full text |Cite
|
Sign up to set email alerts
|

The Drosophila homolog of the human tumor suppressor gene BHD interacts with the JAK-STAT and Dpp signaling pathways in regulating male germline stem cell maintenance

Abstract: Birt-Hogg-Dube´syndrome (BHD) is a rare, inherited genodermatosis characterized by hair follicle hamartomas, kidney tumors and spontaneous pneumothorax. The BHD locus was mapped to chromosome 17p11.2 by linkage analysis, and germline mutations in a novel gene (BHD) were identified in a panel of BHD families. Using RNA interference to decrease expression of the Drosophila BHD homolog (DBHD), we have demonstrated that DBHD is required for male germline stem cell (GSC) maintenance in the fly testis. Reduction of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
31
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(36 citation statements)
references
References 28 publications
5
31
0
Order By: Relevance
“…In Drosophila homologue (DBHD) of the human BHD, folliculin was shown to be required for male germline stem cell maintenance in the fly testis [15]. We speculate here that these results, along with our findings of low-level chromosomal instability (CIN) in oncocytoma and peripheral lymphocytes, may point to a hitherto unrecognized role of the FLCN gene product in maintenance of chromosomal stability.…”
Section: Discussionsupporting
confidence: 51%
“…In Drosophila homologue (DBHD) of the human BHD, folliculin was shown to be required for male germline stem cell maintenance in the fly testis [15]. We speculate here that these results, along with our findings of low-level chromosomal instability (CIN) in oncocytoma and peripheral lymphocytes, may point to a hitherto unrecognized role of the FLCN gene product in maintenance of chromosomal stability.…”
Section: Discussionsupporting
confidence: 51%
“…First, gbb transcription is not affected under the same experimental conditions that cause an increase in dpp mRNA levels. Second, it has been suggested that dpp might function downstream of, or in parallel to, Jak/Stat signalling in Drosophila testes (Singh et al, 2006). Finally, the ectopic expression of Upd in eye discs results in a slight enhancement of dpp mRNA levels (Bach et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…16 Furthermore, deletion of the FLCN homolog in fruit flies disrupts male germ line stem cell maintenance, a defect that appears to be linked to the JAK/STAT (Janus kinase/signal transducer and activator of transcription) pathway. 17 Two folliculin interacting proteins, FNIP1 and FNIP2, were recently isolated. [7][8][9] These factors are broadly expressed in human tissues and specifically associate with folliculin C-terminal domain in ex vivo studies.…”
Section: Introductionmentioning
confidence: 99%